Association between tuberculosis and depression on negative outcomes of tuberculosis treatment: A systematic review and meta-analysis - Ruiz-Grosso P. (2020)
Background Depression is a common comorbidity of tuberculosis (TB) and is associated with poor adherence to treatment of multiple disorders. We conducted a systematic review to synthesize the existing evidence on the relationship between depression and negative outcomes of TB treatment. Methods We systematically reviewed studies that evaluated depressive symptoms (DS) directly or indirectly through psychological distress (PD) and measured negative treatment outcomes of drug-sensitive pulmonary TB, defined as death, loss to follow-up, or non-adherence. Sources included PubMed, Global Health Library, Embase, Scopus and Web of Science from inception to August 2019. Results Of the 2,970 studies initially identified, eight articles were eligible for inclusion and two were used for the primary outcome meta-analysis. We found a strong association between DS and negative TB treatment outcomes (OR = 4.26; CI95%:2.33-7.79; I2 = 0%). DS were also associated with loss to follow-up (OR = 8.70; CI95%:6.50-11.64; I2 = 0%) and death (OR = 2.85; CI95%:1.52-5.36; I2 = 0%). Non-adherence was not associated with DS and PD (OR = 1.34; CI95%:0.70-2.72; I2 = 94.36) or PD alone (OR = 0.92; CI95%:0.81-1.05; I2 = 0%). Conclusions DS are associated with the negative TB treatment outcomes of death and loss to follow-up. Considerable heterogeneity exists in the definition of depression and outcomes such as non-adherence across the limited number of studies on this topic. © 2020 Ruiz-Grosso et al.